Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/pcn.12676
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and psychotropic drug loading in patients with schizophrenia in Asian countries: Fourth survey of Research on Asian Prescription Patterns on antipsychotics

Abstract: Differences in psychiatrist training as well as the civil culture and health insurance system of each country may have contributed to the differences in these rates. The concept of drug loading can be applied to other medical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 30 publications
4
57
1
2
Order By: Relevance
“…The phenotype of mental illness and psychiatric symptoms' manifestation forms have changed throughout eras, cultures, and societies. 5,53,54 From the end of the 19th century to the beginning of the 20th century, Europe experienced a period of great tension between nations and ethnic groups resulting in forms of social chaos. It is during this period that hysteria seemed to be of epidemic proportions, especially among the ladies of society.…”
Section: Emergence Of Hikikomori From the World Historical Viewpointmentioning
confidence: 99%
“…The phenotype of mental illness and psychiatric symptoms' manifestation forms have changed throughout eras, cultures, and societies. 5,53,54 From the end of the 19th century to the beginning of the 20th century, Europe experienced a period of great tension between nations and ethnic groups resulting in forms of social chaos. It is during this period that hysteria seemed to be of epidemic proportions, especially among the ladies of society.…”
Section: Emergence Of Hikikomori From the World Historical Viewpointmentioning
confidence: 99%
“…Consequently, pharmacotherapies for psychiatric disorders in Japan differed from those recommended by treatment guidelines in other countries. [9][10][11][12][13][14] For example, although most guidelines recommended antipsychotic monotherapy for schizophrenia, the number of antipsychotics used in Japan was higher than that used in other countries. In addition, the use of benzodiazepines as adjunctive treatment for major depressive disorder, which is not recommended in most guidelines, was higher in Japan than in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, another nationwide survey on the management of oral anticancer agents in community pharmacies reported that an average of zero or one to five medications were dispensed per week. 24) For most respondents, fewer than 40% of the patients they managed were cancer patients, and the number of cancer patients was not high. This low encounter rate with cancer patients may be related to pharmacists' low rate of board certification, which may result in no association between the success rate for reducing inappropriate medications and the board certification or years of pharmacist experience.…”
Section: Discussionmentioning
confidence: 99%